2019
DOI: 10.1051/0004-6361/201935653
|View full text |Cite
|
Sign up to set email alerts
|

Multi-waveband detection of quasi-periodic pulsations in a stellar flare on EK Draconis observed by XMM-Newton

Abstract: Context. Quasi-periodic pulsations (QPPs) are time variations in the energy emission during a flare that are observed on both the Sun and other stars and thus have the potential to link the physics of solar and stellar flares. Aims. To characterise the QPPs detected in an X-ray flare on the solar analogue, EK Draconis, which was observed by XMM-Newton. Methods. We use wavelet and autocorrelation techniques to identify the QPPs in a detrended version of the flare. We also fit a model to the flare based on an ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…To date, stellar flare QPPs at several wavelengths within the same spectral range have been observed in optical (e.g. Zhilyaev et al, 2000, see Section 3.1.1), radio (see Section 3.2) and soft Xrays (Broomhall et al, 2019b, see Section 3.3.2). However, no QPPs occurring simultaneously in different spectral ranges (e.g.…”
Section: On Multiwavelength Observations Of Stellar Flare Qppsmentioning
confidence: 87%
See 1 more Smart Citation
“…To date, stellar flare QPPs at several wavelengths within the same spectral range have been observed in optical (e.g. Zhilyaev et al, 2000, see Section 3.1.1), radio (see Section 3.2) and soft Xrays (Broomhall et al, 2019b, see Section 3.3.2). However, no QPPs occurring simultaneously in different spectral ranges (e.g.…”
Section: On Multiwavelength Observations Of Stellar Flare Qppsmentioning
confidence: 87%
“…The two consecutive flares were consistent with the reheating of the same magnetic structure where the first flare occurred. The large-scale magnetic structure and the periodicity of the multiple gigantic stellar flares suggested that the reheating events of the same magnetic stellar loop could develop during an interaction between the star and the disk of the star owing to their differential rotation Broomhall et al (2019b). detected QPPs in a flare on EK Draconics in the Xray bands of low-energy (0.2 -1.0 keV) with a period of 76±2 min and high-energy (1.0 -12.0 keV) with a period of 82±2 min.…”
mentioning
confidence: 99%
“…The term describes a series of reconnection events associated with periodic changes in the magnetic connectivity and topology of the field, the periodicity of which is derived from the relaxation of a perturbed field from a finite, aperiodic driver. As a mechanism, oscillatory reconnection has been proposed as a possible driving force behind quasi-periodic pulsations (QPPs) of solar flares (e.g., Kupriyanova et al 2016;Van Doorsselaere et al 2016;Pugh et al 2017;Yuan et al 2019;Hayes et al 2020;Li et al 2020aLi et al , 2020bLi et al , 2021Clarke et al 2021) and stellar flares (e.g., Broomhall et al 2019;Guarcello et al 2019;Jackman et al 2019;Notsu et al 2019;Vida et al 2019;Mancuso et al 2020;Ramsay et al 2021). Detailed reviews of a wide variety of suggested mechanism(s) behind QPPs can be found in McLaughlin et al (2018), Kupriyanova et al (2020), and Zimovets et al (2021).…”
Section: Introductionmentioning
confidence: 99%
“…Empirical properties of QPP in solar and stellar flares have similarities (Cho et al 2016) which could indicate the analogy in underlying physical processes. In particular, QPP in stellar flares have been detected at different wavelengths within the same spectral band: in optics (Zhilyaev et al 2000), in radio (Stepanov et al 2001), and in SXR (Broomhall et al 2019a). Guarcello et al (2019) analysed simultaneous observations of stellar superflares in the WL (with Kepler) and SXR (with XMM-Newton), and found 500-s QPP in an SXR flare lightcurve on the M2 class star HCG 273.…”
Section: Introductionmentioning
confidence: 99%